Trends in Apomixis Research: The 10 Most Cited Research Articles Published in the Pregenomic and Genomic Eras - Palumbo, Fabio; Draga, Samela; Vannozzi, Alessandro; Lucchin, Margherita; Barcaccia, Gianni (Frontiers in Plant Science, 2022)
Apomixis, or asexual reproduction by seed, represents an easy shortcut for life cycle renewal based on maternal embryo production without ploidy reduction (meiosis) and ploidy restitution (syngamy). Although the first studies officially published on this topic in scientific journals date back to the early 1930s, the identification and introduction of genes involved in asexual reproduction in species of agronomic interest still represent a major challenge. Through a bibliometric analysis of the research programs implemented in apomixis over the last 40 years, the present study was aimed to discuss not only the main findings achieved but also the investigational methods and model species used. We split the critical survey of the most cited original articles into pregenomic and genomic eras to identify potential trends and depict scenarios that have emerged in the scientific community working on apomixis, as well as to determine any correlation between the exponential increase in acquired basic knowledge and the development of advanced analytical technologies. This review found a substantial stagnation in the use of the same model species, with few exceptions, for at least 40 years. In contrast, the development of new molecular techniques, genomic platforms, and repositories has directly affected the approaches used in research, which has been directed toward an increasingly focused study of the genetic and epigenetic determinants of apomixis.